1974
DOI: 10.1159/000260103
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Uptake in vivo by Deciduous Enamel of Children from Neutral Fluoride and APF Mouthrinses

Abstract: 173 exfoliated teeth were collected from three groups of children, age 9–10 years, who for three school years used daily one of three mouthrinses consisting of (a) 200 ppm F, 0.1 m phosphate at pH 4.0, (b) 200 ppm F at pH 7.0, or (c) a placebo rinse. The average F concentration at 5 μm in 58 placebo treated teeth was 595 ppm. After approximately 190 rinses, the average F concentration at 5 μm for the pH 7 and pH 4 fluoride rinse groups was 616 and 677 ppm, respectively. The difference between the control and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…A larger accumulation of plaque on teeth could inhibit fluoride uptake more from a dilute F rinse than from a relatively concentrated rinse. It is of interest to note here that an almost identical low fluoride uptake was observed from daily use of the same 0.02% F rinse in anoth er non-fluoride area [Mellberg and N icholson, 1973].…”
Section: Discussionsupporting
confidence: 58%
“…A larger accumulation of plaque on teeth could inhibit fluoride uptake more from a dilute F rinse than from a relatively concentrated rinse. It is of interest to note here that an almost identical low fluoride uptake was observed from daily use of the same 0.02% F rinse in anoth er non-fluoride area [Mellberg and N icholson, 1973].…”
Section: Discussionsupporting
confidence: 58%
“…Because of the large standard deviations, this increase was not statistically significant (p > 0.25). This result appears to be in harmony with a previous in vivo study (Mellberg and Nicholson, 1974), which showed that rinses with a solution consisting of 200 ppm F at pH 7 did not significantly increase the permanentlybound fluoride content of the enamel.…”
Section: Discussionsupporting
confidence: 91%
“…Since these fluoride rinses do not substantially increase the enamel fluoride content on a long-term basis (Mellberg and Nicholson, 1974), the effectiveness of the rinse regimen appears to come from the relatively high levels of fluoride in the oral fluids produced by the frequent fluoride rinses.…”
Section: Introductionmentioning
confidence: 99%
“…Other in vitro studies (Hong et al, 1985) and in vivo studies (Mellberg and Nicholson, 1974;Shern et al, 1984) have shown that repeated short applications of 0.2% NaF can cause incorporation of some permanently bound F into the enamel. Also consistent with the results of previous in vitro studies (Takagi et al, 1984;Hong et al, 1985) and in vivo studies (Shern et al, 1979;Chow et al, 1981;Shern et al, 1984) is the present finding that the experimental specimens, which received the same F regimen as did the controls plus a DCPD-forming treatment, incorporated much more F into the enamel than did the controls.…”
Section: Discussionmentioning
confidence: 98%